Propuesta de implementación de la metodología LEAN MANUFACTURING en las lineas de producción del proceso de fabricación de telas de polipropileno en la planta de Geosistemas PAVCO. (2023)
In the present investigation reference is made to the productivity, in the fabrics of polypropylene at the Geosistemas Pavco plant, reaching the national and international markets. international, competitively and meet the needs of customers, with high quality standards and favorable prices for the final consumer in the context of innovation, with which seeks to propose options for improvements in the production lines to reduce the waste through a process improvement methodology.